2017
DOI: 10.1080/14767058.2017.1373084
|View full text |Cite
|
Sign up to set email alerts
|

Fetal heart rate changes observed on the CTG trace during instrumental vaginal delivery

Abstract: After application of instruments, 90% of CTG traces showed abnormal features. Tachycardia, baro- and chemoreceptor-mediated decelerations, and saltatory patterns were the most common abnormalities. Increased baseline FHR during vacuum as compared to forceps delivery was possibly secondary to pain/pressure and resultant sympathetic overactivity. The saltatory pattern was more common in forceps deliveries, possibly secondary to increased intracranial pressure and resultant autonomic instability. Despite these CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…First, we assessed the association between marked variability and neonatal acidosis in a population of women with spontaneous vaginal deliveries. Indeed, it has been suggested that marked variability could be induced by instrumental delivery through increased intracranial pressure 21 . Therefore, this analysis aimed to verify that the association remained unchanged in a population where marked variability cannot be a consequence of an instrumental delivery.…”
Section: Methodsmentioning
confidence: 94%
“…First, we assessed the association between marked variability and neonatal acidosis in a population of women with spontaneous vaginal deliveries. Indeed, it has been suggested that marked variability could be induced by instrumental delivery through increased intracranial pressure 21 . Therefore, this analysis aimed to verify that the association remained unchanged in a population where marked variability cannot be a consequence of an instrumental delivery.…”
Section: Methodsmentioning
confidence: 94%
“…Furthermore, the pathophysiologic changes that mediate increased FHRV during labour remain poorly understood 34–38 . There is a lack of consensus on factors associated with increased FHRV during labour 27–30,39–42 . Moreover, the clinical significance of increased FHRV is uncertain 27,43,44 …”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38] There is a lack of consensus on factors associated with increased FHRV during labour. [27][28][29][30][39][40][41][42] Moreover, the clinical significance of increased FHRV is uncertain. 27,43,44 The aims of the present review are to delineate the pathophysiology of increased FHRV, clarify the related terminology, and elucidate its potential clinical utility.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with published literature as for the last 15 years, the most frequent indication for OVD in modern obstetrics is fetal distress. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%